Studi Kepustakaan Analisis Bendungan Lere di Pulau Sabu, Kabupaten Sabu-Raijua, Propinsi NTT - Laurentia, Susilawati Cicilia; Purwantini, Purwantini; Sidiq, Alif Lombardoaji (Department of Civil Engineering, Diponegoro University, 2025)
Sabu Island, Sabu-Raijua Regency, is dry area, recorded having Lere Dam, which is no functioning, caused by a sinkhole in the inundation area, and the water disappears immediately becomes dry. The dam rehabilitation requires a desk-study for the potential agriculture and raw water produced. The study methodology includes: monitoring the existing dam; monitoring results analysis consisting of hydrological, geographical analysis and river basin simulation; recommendations for the axis location of the dam with its optimal and effective storage capacity. The results of the geographical analysis and simulation, show that the location of the main dam axis needs to be shifted upstream at the axis position from 10029'41.86